Expansionismo brasileiro na Argentina - Gramasco, Thiago Bastelli [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The objective will be to analyze the relationship between Brazil and Argentina during the governments of the PT. During the Lula government the issue of development was heavily associated with the South American regional integration. And the process of internationalization of the Brazilian economy grew supported by Brazilian public funding, especially from BNDES. Saw the advancement of acquisitions, mergers, associations abroad by large companies such as Odebrecht, Andrade Gutierrez, Camargo Corrêa, Votorantim, Gerdau, JBS / Friboi, Marfrig, Petrobras, Vale and others; in addition to infrastructure projects involving the Brazilian construction companies. In the sector of primary resources, the Asian demand helped stimulate this expansionist process in view of the rise in international commodity prices and earnings prospects through the control of natural resources in the region. In turn, the provision of services in construction / engineering for large contractors was stimulated by public loans, in a context of demand from neighboring countries and availability of funds from the BNDES. But investments are not restricted to the sector of commodities and great engineering, especially in the case of Argentina, where Brazilian investments are quite diversified. However, as this expansionist process, which can be conducive to regional integration has been economically / commercially more favorable to Brazil, according to government officials and many analysts, has been producing discontent and accusations of imperialism (or sub-imperialism) to the country. Nevertheless, the strengthening of economic and trade relations can contribute to advances in the integration of infrastructure and political and institutional field. The focus is the study of expansionism of Brazilian companies over South America, with emphasis on the case of Argentina, the country that received Brazilian direct investment during the Lula government. The study investigates...

O objetivo do trabalho será analisar as relações entre Brasil e Argentina durante os governos do PT. Durante os governos Lula a temática do desenvolvimento esteve bastante associada à da integração regional sul-americana. E o processo de internacionalização da economia brasileira cresceu apoiado em financiamentos públicos brasileiros, do BNDES em especial. Assistiu-se ao avanço de aquisições, fusões, associações no exterior por grandes empresas como Odebrecht, Andrade Gutierrez, Camargo Corrêa, Votorantin, Gerdau, JBS/Friboi, Marfrig, Petrobras, Vale entre outras; além das obras de infraestrutura envolvendo as construtoras brasileiras. No setor de recursos primários a demanda asiática contribuiu para estimular esse processo expansionista, tendo em vista a alta nos preços internacionais das commodities e as perspectivas de lucros por meio do controle de recursos naturais na região. Por sua vez, a prestação de serviços no setor de construção/engenharia pelas grandes empreiteiras foi estimulada pelos empréstimos públicos, num contexto de demanda dos países vizinhos e disponibilidade de recursos junto ao BNDES. Mas os investimentos não se restringem ao setor das commodities e serviços de grande engenharia, sobretudo no caso da Argentina, onde os investimentos brasileiros são bastante diversificados. Entretanto, como esse processo expansionista tem sido economicamente/comercialmente bem mais favorável ao Brasil, segundo governantes e analistas diversos, vem produzindo descontentamentos e acusações de imperialismo (ou subimperialismo) ao país. Não obstante, o estreitamento das relações econômico-comerciais pode contribuir para com avanços da integração da infraestrutura e no campo político-institucional. O foco é o estudo do expansionismo de empresas brasileiras sobre a América do Sul, com ênfase sobre o caso argentino, país que mais recebeu investimentos diretos brasileiros durante os governos Lula...
Keywords: Geografia politica; Política econômica; Brasil - Relações exteriores; Brasil; Argentina; América do Sul